3(3x+2)=6(2x-3)

Simple and best practice solution for 3(3x+2)=6(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x+2)=6(2x-3) equation:


Simplifying
3(3x + 2) = 6(2x + -3)

Reorder the terms:
3(2 + 3x) = 6(2x + -3)
(2 * 3 + 3x * 3) = 6(2x + -3)
(6 + 9x) = 6(2x + -3)

Reorder the terms:
6 + 9x = 6(-3 + 2x)
6 + 9x = (-3 * 6 + 2x * 6)
6 + 9x = (-18 + 12x)

Solving
6 + 9x = -18 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
6 + 9x + -12x = -18 + 12x + -12x

Combine like terms: 9x + -12x = -3x
6 + -3x = -18 + 12x + -12x

Combine like terms: 12x + -12x = 0
6 + -3x = -18 + 0
6 + -3x = -18

Add '-6' to each side of the equation.
6 + -6 + -3x = -18 + -6

Combine like terms: 6 + -6 = 0
0 + -3x = -18 + -6
-3x = -18 + -6

Combine like terms: -18 + -6 = -24
-3x = -24

Divide each side by '-3'.
x = 8

Simplifying
x = 8

See similar equations:

| 9x+3=7x-19 | | 2+15+15v=62 | | 40r^2-35r+16r-14=0 | | 50m+42750=42675-175m | | 4(2x-7)=3(x-1) | | 5y+35=x+5 | | G(10)=50 | | 7x-47=x | | G(7)=98 | | 8x+23=3x+128 | | 20(-2+x)+10=50(-1+4x) | | 8x-10=7x-5 | | F(4)=96 | | V^2+(6.6V)-51.48=0 | | a-152= | | y+.5= | | 10(-2+x)+10=50(-1+4x) | | 8w+4=24 | | 5x+4=5+2x+24 | | x^2+19x+32=0 | | x^2-(4+p)x+12=0 | | 3n+5/7= | | 9x^2-8x-71=0 | | 3x-8x+3=x-8+11 | | 3(x-5)=2(x+10) | | 9k+4+7d= | | 0.05+0.10(100-x)=0.45x | | 49+-10= | | 5w-4=3w+2 | | 6x-6=6+2x | | -6(7x+9)=8(9x-4) | | 5x+6=3-2(4) |

Equations solver categories